A Conceptual Level on Green Computing Applications on Eco-Friendly Approaches - Dr. C. A. Anuradha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Green computing will work in this field as a life saver to environment as green computing will reduce energy usage by using various green computing eco-friendly approaches like-green design, green awareness, green standards, green disposals, green manufacturing and green usage which therefore help in the less emission. The "Going Green" is a rising trend establishing itself as the preferred way of doing things while saving the environment. This now appears in a large number of aspects in our lives, such as recycling, energy-efficient devices, clean energy sources, eco-friendly vehicles, green buildings. Computing has also established its share to contribute to saving the environment under the concept "Green Computing". Green computing is the environmentally responsible and eco-friendly use of computers and their resources. In broader terms, it is also defined as the study of designing, engineering, manufacturing, using and disposing of computing devices in a way that reduces their environmental impact. Green Computing, also known as Green Technology or Green IT, has quickly emerged as the most effective means of utilising technology.
Keywords: Green Computing; Green Technology; Applications; Eco- Friendly Approaches